2020
DOI: 10.3390/catal10030279
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Morphology on the Photoelectrochemical Activity of TiO2 Self-Organized Nanotube Arrays

Abstract: In the present work, highly ordered titanium dioxide (TiO 2 ) nanotube anodes were grown using a rapid anodization process. The photoelectrochemical performances of these electrodes strongly depend on the anodization conditions. Parameters such as electrolyte composition, anodization potential and anodization time are shown to affect the geometrical parameters of TiO 2 nanotubes. The optimal anodization parameters are determined by photocurrent measurements, linear sweep voltammetry and electrochemical impedan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…A great effort has been spent on the optimization of the morphology of nanotubes, since PEC tests showed that besides crystallinity, length, pore diameter and wall thickness critically affect photoelectrochemical activity [ 173 , 174 ]. Indeed, PAs made of nanotubes with small pore diameters exhibit low photocurrent, and the phenomenon is explained by the hindered diffusion of the electrolyte solution into the tubes [ 151 , 175 , 176 , 177 ] and the higher charge transfer resistance. As regards the wall thickness, thin-walled (3–5 nm) nanotubes facilitate the diffusion of the photogenerated holes to the semiconductor/electrolyte interface during water splitting, allowing for efficient separation of charges [ 145 , 176 ]; also, porous-wall nanotubes were used in PEC devices, showing a good photoconversion efficiency [ 178 ], thanks to the increased surface area.…”
Section: Photoelectrochemical Water Splittingmentioning
confidence: 99%
See 1 more Smart Citation
“…A great effort has been spent on the optimization of the morphology of nanotubes, since PEC tests showed that besides crystallinity, length, pore diameter and wall thickness critically affect photoelectrochemical activity [ 173 , 174 ]. Indeed, PAs made of nanotubes with small pore diameters exhibit low photocurrent, and the phenomenon is explained by the hindered diffusion of the electrolyte solution into the tubes [ 151 , 175 , 176 , 177 ] and the higher charge transfer resistance. As regards the wall thickness, thin-walled (3–5 nm) nanotubes facilitate the diffusion of the photogenerated holes to the semiconductor/electrolyte interface during water splitting, allowing for efficient separation of charges [ 145 , 176 ]; also, porous-wall nanotubes were used in PEC devices, showing a good photoconversion efficiency [ 178 ], thanks to the increased surface area.…”
Section: Photoelectrochemical Water Splittingmentioning
confidence: 99%
“…Regarding the tube length, many papers report on the study of the optimal length to obtain a high PEC performance, but a wide consensus on this parameter is still missing due to discordant results, even though it is clear that a compromise between η interface and η transport is needed [ 175 ]. Generally speaking, the 1D nanostructuring is less effective than 0D for the increase of the specific surface area; so, if compared to electrodes made of 20 nm diameter beads, electrodes made of nanotubes (wall thickness 20 nm, inner diameter 10 nm) should be thicker by a factor of 2 to recover the same specific surface, but increasing the tube length affects electrolyte diffusion and enhances the requirements on conduction properties, although improving the light absorption at longer wavelengths.…”
Section: Photoelectrochemical Water Splittingmentioning
confidence: 99%
“…The existence of several concerns related to the increasing energy demand and the related environmental crisis [1][2][3][4][5][6] indicates the need to identify innovative, effective and low cost solutions. Photoelectrochemical water splitting (PWS) [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] is recognised as a promising strategy and it attracts particular interest for storing solar energy into the chemical bonds of hydrogen as fuel [26][27][28], which can be further utilised in fuel cells [29][30][31][32][33][34], internal combustion engines and to progressively decarbonize industrial processes [35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…In several reports, the photo-electrochemical properties of TiO 2 nanoelectrodes were investigated with the aim to study their electronic structure and photoefficiency through electrochemical measurements [27][28][29]. In particular, the research on the electrochemical properties of TiO 2 electrodes pointed out that the photoefficiency depends on the particle morphology, including size and shape [30][31][32][33]. In fact, nanoparticle shape and preferential surface orientation of its facets play an important role in the electrochemical oxidation because these factors affect not only the reactants but also the interfacial charge transfer.…”
Section: Introductionmentioning
confidence: 99%